Pierson and Fairchild's principles & techniques of patient care - Fairchild, Sheryl L.; Pierson, Frank M. (Elsevier, 2013)
"Learn how to effectively assess and manage patients in the rehabilitation setting with this new, visually enhanced edition. In addition to clear, "how-to" information on positioning and draping the patient,patient transfer, ambulation activities, and more, you'll gain insight into the rationales and physiological principles explaining why specific techniques are used.This fourth edition is an excellent resource for developing problem-solving strategies needed to address real-world situations."--BOOK JACKET